Representation Degree of the first circle pupils of primary teaching to the values of citizenship in the context of the Syrian crisis (A filed study on a sample of pupils in the city of Lattakia) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to determine the degree of representation of  the first circle pupils of primary teaching to the values of citizenship in the context of the Syrian crisis according to variables : the kind of staying (A comer  pupil -A habitant  pupil )and family state (martyr's son ), but to achieve this, a questionnaire was developed to included(35) paragraphs to measure the degree of representation of  the pupils  to the  values of citizenship , and applied on a sample of (240) pupils. By depending on the suitable statistic ways, the  study found that the degree represents  pupils for citizenship  values were middle , and the highest value was rights and duties and the next was the values of respecting others and acceptation the difference with middle degree ,then the values of belonging, lastly participation and interaction with middle degree the study also found  that  there is statistically significant difference at the  level of significance (α ≥ 0.05) between pupils' degree on all the axis of the questionnaire according to the variable of the kind of staying exception  for the interaction and  participation, and it is for emigrants  ,and the study also found  that  there isn't statistically significant difference at the  level of significance (α ≥ 0.05) between pupils' degree  according to the variable of family state.